2020
DOI: 10.1111/mmi.14651
|View full text |Cite
|
Sign up to set email alerts
|

A key cytosolic iron–sulfur cluster synthesis protein localizes to the mitochondrion of Toxoplasma gondii

Abstract: Iron–sulfur (Fe‐S) clusters are prosthetic groups on proteins that function in a range of enzymatic and electron transfer reactions. Fe‐S cluster synthesis is essential for the survival of all eukaryotes. Independent Fe‐S cluster biosynthesis pathways occur in the mitochondrion, plastid, and cytosolic compartments of eukaryotic cells. Little is known about the cytosolic Fe‐S cluster biosynthesis in apicomplexan parasites, the causative agents of diseases such as malaria and toxoplasmosis. NBP35 serves as a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(69 citation statements)
references
References 61 publications
6
63
0
Order By: Relevance
“…It should be noted that although we believe the drop in mitochondrial membrane potential is likely due to a specific alteration of the respiratory chain, it may also be due to a loss of parasite viability. Reassuringly, our results are in line with the recent findings obtained by Aw et al, who generated a mutant of mitochondrial Fe-S cluster synthesis (by depleting TgNFS1), and observed a sharp decrease in TgSDHB abundance and a clear drop in mitochondrial O 2 consumption rate [25].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It should be noted that although we believe the drop in mitochondrial membrane potential is likely due to a specific alteration of the respiratory chain, it may also be due to a loss of parasite viability. Reassuringly, our results are in line with the recent findings obtained by Aw et al, who generated a mutant of mitochondrial Fe-S cluster synthesis (by depleting TgNFS1), and observed a sharp decrease in TgSDHB abundance and a clear drop in mitochondrial O 2 consumption rate [25].…”
Section: Resultssupporting
confidence: 92%
“…Accordingly, perhaps the most obvious consequence of disrupting the ISC pathway was the profound impact on the mitochondrial respiratory capacity, as evidenced experimentally by measuring the mitochondrial membrane potential (Figure 8D), and supported by quantitative analyses showing a clear drop in expression of many respiratory complex proteins (Figure 8A, B, and C, Table S4). This is also in line with the recent description of another mitochondrial Fe-S cluster synthesis mutant that showed a marked alteration of its respiratory capacity [25]. Although the mitochondrion, through the TCA cycle and the respiratory chain/oxidative phosphorylation, contributes to energy production in tachyzoites [91], the glycolytic flux is also believed to be a major source of carbon and energy for these parasites [92].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In common with most eukaryotes, elemental analysis found that around 5% of the atoms of T. gondii atoms are iron (Al-sandaqchi et al, 2018). This iron is required for a number of essential cellular processes, including heme biosynthesis (Bergmann et al, 2020;Kloehn et al, 2020), iron sulphur (Fe-S) cluster biogenesis (Aw et al, 2020), and as a cofactor in several important proteins such as catalase (Kwok et al, 2004;Odberg-Ferragut et al, 2000), prolyl hydroxylases (Florimond et al, 2019) and the deoxyribonucleotide synthesis enzyme ribonucleotide reductase. Iron acquisition and use have been studied in various pathogenic parasites such as Trichomonas (Sehgal et al, 2012) and in some detail in kinetoplastids such as Leishmania (Zaidi et al, 2017) and Trypanosoma (Carbajo et al, 2021).…”
mentioning
confidence: 99%